EXPANDED CORE CURRICULUM FOR STUDENTS WITH VISUAL IMPAIRMENT (Годишен зборник на Филозофски факултет - Скопје, 2021)
Historically, special educators and rehabilitators have found that the traditional curriculum in inclusive schools is not sufficient for students with severe visual impairment. In the educational process, in order to compensate for vision loss, the socalled expanded core curriculum must be included in their education. By applying for this program, students with visual impairment will achieve the same educational outcomes as their sighted peers.In addition to the traditional school subjects, the expanded core curriculum also provides special subjects for the development of compensatory skills in students with visual impairment. The aim of the program is for students with visual impairments to finish school with the necessary knowledge and skills for independent living. In the system of inclusive education, this program is realized by the special educator and rehabilitator. This paper will explain the components of the expanded core curriculum for students with severe visual impairment.